ANALISIS PERBEDAAN ABNORMAL RETURN DAN BID-ASK SPREAD PADA SAHAM SEBELUM DAN SESUDAH AKSI KORPORASI STOCK SPLIT DI BURSA EFEK INDONESIA: ANALISIS PERBEDAAN ABNORMAL RETURN DAN BID-ASK SPREAD PADA SAHAM SEBELUM DAN SESUDAH AKSI KORPORASI STOCK SPLIT DI BURSA EFEK INDONESIA - Ayu Utari, Ni Made; Dwijayanti, Ni Made Ayu; Oka Sudiadnyani, I Gusti Agung (Universitas Mercu Buana Yogyakarta, 2023)
Stock splits is corporate actions carried out by companies in the capital market. Stock splits are said to be cosmetic only, because they will not affect the company's cash flow and the proportion of investor ownership. However, other researchers stated that stock splits not affect the company's cash flow and share capitalization value. Based on research gap, the abnormal return and bid-ask spread variables are used to analysis the market reaction to the stock split. This type of research is quantitative comparative. The study population consisted of 834 stocks from companies in all sectors listed on the Indonesia Stock Exchange for the period 2020 to 2023. The number of samples selected was based on a purposive sampling technique of 24 stocks. Data obtained via the Indonesian Stock Exchange website. The market adjusted model is the calculation method chosen to calculate the expected return value. The data analysis technique used is descriptive statistical analysis, classic assumption test and hypothesis testing which is Paired Sample T-Test and Wilcoxon Signed Ranks Test. The results of the research are there were differences in abnormal returns and bid-ask spreads stock before and after stock split corporate actions. The results of this study are in line with signal theory, where stock split information is well received by stockholders on the stock market and in line with the trading range theory which suggests that stock splits will provide an increase in stock liquidity due to the increasing shareholder interest in making share purchase transactions